Ultrastructural and Immunofluorescent Analysis of Lithium Effects on Autophagy in Hepatocellular Carcinoma Cells - Taskaeva, Iuliia; Bgatova, Nataliya (Asian Pacific Journal of Cancer Biology, 2018)
Background: Hepatocellular carcinoma (HCC) is one of the most malignant cancers worldwide. The role of autophagy in the НСС development and progression is controversial and are still not well known. It has been shown that lithium induces autophagy and apoptosis, affects on proliferation and survival of various human malignancies. In this study we estimated lithium`s effects on autophagy in HCC in vivo. Materials and methods: Subcellular components and autophagic vacuoles were analyzed by transmission electron microscopy. The number of cells with LC3 and LAMP1 punctate was analyzed by double-immunofluorescence staining. Data are presented as mean ± standard deviation (SD). Mann–Whitney nonparametric tests were used to assess statistically significant differences at P < 0.05. Results: Lithium carbonate increased the numerical and volume density of autophagic vacuoles and autophagy marker LC3 beta. Therefore, lithium carbonate promotes enlarged autophagic vacuoles formation in HCC cells in vivo. Conclusion: Extended and unresolved autophagy induces cancer cell death by stimulating autophagic cell death. Thus, lithium-mediated autophagy can be an attractive approach in HCC chemotherapy.